Onsite Versus Remote Working: The Impact on Satisfaction, Productivity, and Performance of Medical Call Center Workers - Amjad Alfaleh MBBS, SBFM, ABFM; Abdullah Alkattan Pharm.D; Alaa Alageel BSc; Mohammed Salah MBBS, MSc; Mona Almutairi Pharm.D; Khlood Sagor MBBS; Khaled Alabdulkareem MBBS, SBFM, ABFM (SAGE Publishing, 2021)
Job satisfaction is determined as the measure to know the individuals' feelings toward their work. The working conditions that can affect satisfaction and performance of the call center agents have received particular concern. This study aimed to determine the role of remote call center working on agents' satisfaction compared to onsite workers. A cross-section study was conducted between December 2020 and April 2021 that include 124 agents working in a governmental medical call center in Saudi Arabia. Each agent was receiving a questionnaire that investigates his/her satisfaction with the job nature, supervisor support, job autonomy, job productivity, and performance. Seventy-seven physicians working onsite were compared to forty-seven physicians remotely working in the medical call center. The mean age of the physicians included was 43.17 ± 8.4 years, and most of them were male (>70%), married (>85%), and family medicine specialists (>50%). The mean years of experience in the medical field of the physicians included was 16.87 ± 8.07 years, and the mean years of experience in the medical call center was 1.44 ± .97 years. Onsite agents were more satisfied concerning job nature, supervisor support, productivity, and performance compared to remote agents (70.82 vs 53.47%, 63.38 vs 55.05%, and 66.51 vs 56.03%, respectively). However, onsite agents were less satisfied regarding job autonomy than remote physicians (46.81 vs 53.19%, P -value = .128). Overall, general satisfaction was more seen in physicians working onsite as opposed to remote workers in the medical call center in Saudi Arabia (64.90 vs 54.25%, P -value < .01).